Phylogeny and mycotoxin profiles of pathogenic Alternaria and Curvularia species isolated from date palm in southern Tunisia - Rabaaoui, Amal; Masiello, Mario; Somma, Stefania; Crudo, Francesco; Dall’Asta, Chiara; Righetti, Laura; Susca, Antonia; Logrieco, Antonio Francesco; Namsi, Ahmed; Gdoura, Radhouane; Werbrouck, Stefaan P. O.; Moretti, Antonio (Frontiers in Microbiology, 2022)
Date palm (Phoenix dactylifera L.), is widely cultivated crop across North Africa, with about 300 thousand tons of fruits produced per year, in Tunisia. A wide range of fungal pathogens has been associated with leaf spots of date palm, being Alternaria species the most frequent reported. Symptomatic leaves of Deglet Nour variety were randomly collected in six localities in Tunisia. Based on morphological features, we used a polyphasic approach to identify 45 Alternaria and five Curvularia strains, confirming their pathogenicity. Sequencing of allergen-alt-a1, glyceraldeyde3-phosphate-dehydrogenase (gpd) and calmodulin genes allowed us to group 35 strains in Alternaria Section, and 10 strains in Ulocladioides Section. Based on sequencing analyses of Internal Transcribed Spacer, gpd and elongation factor genomic regions, all Curvularia strains were identified as Curvularia spicifera. All Alternaria and Curvularia species tested on date palm plantlets proved to be pathogenic, fulfilling Koch’s postulates. Among the species, although no significant difference was observed, A. arborescens was the most aggressive, while C. spicifera resulted to be the less aggressive. The capability of these strains to produce in vitro mycotoxins was evaluated. None of the A. consortialis strains produced any known Alternaria mycotoxin, whereas more than 80 % of the strains included in Alternaria section produced variable amounts of multiple mycotoxins such as alternariol, alternariol monomethyl ether, altenuene, tenuazonic acid, tentoxin. Curvularia spicifera strains produced few detectable traces of fumonisins B. This work reports a first comprehensive multidisciplinary study of mycotoxigenic Alternaria species and C. spicifera associated with leaf spot disease on date palm.